Development of Rapid and Low-cost Paper Based Sensing Platform for Bacterial Detection. (2017) - Alhogail, Sahar; Suaifan, Ghadeer A.R.Y.; Zourob, Mohammed
Abstract: The development of highly sensitive and specific colorimetric biosensor for pathogens spot detection is currently researchers challenge. This study illustrates the design and development of specific peptide probe for the detection of specific proteases secreted from pathogens. These proteases precisely cleaved specific peptide substrate labeled with nano-magnetic beads and attached to gold sensing surface. The superiority of this approach is based on its low-cost, simplicity being colorimetric, can be run by unskilled personnel and can be applied to real samples (without the need for isolation or purification) in short time (1-5 minute). Furthermore the test can be printed/fabricated on personal healthcare.